Rattus hoogerwerfi Chasen 1939 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus hoogerwerfi Chasen, 1939. Treubia, 17(3):496. TYPE LOCALITY: Indonesia, Sumatra, Atjeh, Blang Kedjeren, 2900 ft. (884 m). DISTRIBUTION: Sumatra. COMMENT: Listed as a species by Misonne, 1969, Ann. Mus. R. Afr. Cent. Tervuren, ser. 8, Sci. Zool., 172: 132, Corbet and Hill, 1980:173, and Musser, 1981, Zool. Verhandelingen, 189:30. ISIS NUMBER: 5301410011058050001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 550, DOI: 10.5281/zenodo.7353037